UNESCO Factors Affecting Building Phayao Learning City of Thailand: An Opinion from the Senior Citizens - Teeranon, Phanintra; Phrueksawatnon, Piyada; Kaowiwattanakul, Sukanya (Connexion: Journal of Humanities and Social Sciences, 2021)
UNESCO promotes learning cities and lifelong learning to assure sustainable resilience of community in a fast changing world. There are six dimensions affecting building a learning city according to UNESCO: planning, involvement, accessibility, monitoring and evaluation, celebration, and funding. Phayao Learning City has applied these dimensions in this framework, and this paper analyses the opinion of senior citizens in Phayao Province’s about UNESCO’s input on Phayao Learning City. There were 34 senior Phayao citizens who answered questionnaires derived from UNESCO’s factor affecting Learning City. The statistical analysis of mean, S.D., and causal relationship were calculated. Another 15 subjects were asked to participate in the interview. Thematic analyses with theme-rhyme analysis were used for the interview data. The results, unlike most previous studies, have shown that the seniors mentioned ‘Accessibility’ as the most important factor for both lifelong learning and learning city. This factor received a positive direct effect (DE) (DE = 0.843) from ‘Celebration’ and positive indirect effect (IE) from ‘Planning’ (IE = 0.329) and ‘Involvement’ (IE = 0.195). On the contrary, ‘Funding’ showed a negative direct effect on ‘Accessibility’ (DE = -0.269). This means that funding is a hidden obstacle on building Phayao Learning City. The interview’s results also supported data from the questionnaires. The results suggested that building Phayao Learning City requires a combination of factors.